Analysis of Factors Affecting The Income of Street Trader - Herman Herman; Yulia Harwina (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2023)
The aim of this research is to find out what factors influence the income of street vendors from Panam-Pekanbaru (Case Study: Push/Porch Cart Vendors). Methodology/approach – the data in this study were collected through a questionnaire, the total sample was 99 respondents with a purposive sampling technique. data analysis techniques using the classical assumption test, multiple linear regression analysis and hypothesis testing. Findings – The results of the study show that the variables that have a significant effect on the income of traders are experience (X1), prices (X3) and sales (X5), while the variables that do not have a significant effect on the income of traders are labor (X2), working hours (X4). While the results of the F test that all independent variables have a significant effect on the dependent variable. And the magnitude of the influence of the independent variable on the dependent variable is 94.56 percent while the remaining 5.44 percent is influenced by other variables outside the research. Novelty/value – that the factors that affect traders' income are experience, price and sales results. Key words : experience, labor, price, working hours, sales and income.